Public target selection and family firms - Ezgi H. Ottolenghi (The Journal of Entrepreneurial Finance (JEF), 2023)
We examine the relation between ownership structure and M&A target selection when family firms pursue public firm acquisitions. We find that family firm acquirers select targets that have lower Tobin's Q relative to non-family acquirers. Our results suggest that family firms choose to acquire less glamorous targets against which they can better negotiate. The market reacts more positively to these family firm acquisitions at announcement and out to one year. It is family firm target selection skill along with negotiation skill that leads to the favorable market reception.
Keywords: G32; G34; 650; family firm; founder; mergers and acquisitions; target selection; ownership